Iron(III) catalyzed halo-functionalization of alkynes. Issue 27 (1st July 2015) - Catano, Bryant; Lee, John; Kim, Claudia; Farrell, David; Petersen, Jeffrey L.; Xing, Yalan
Graphical abstract: Abstract: Aromatic and aliphatic alkynes can be halo-functionalized to α, α-dihalodimethyl ketals catalyzed by FeCl3 in excellent yields. MeOH is used as a nucleophilic solvent and N -halosuccinimide as the halogen source for this efficient transformation. The resulting α, α-dibromodimethyl ketals can be converted to the corresponding α, α-dibromoketones by treatment with 8% FeCl3 in silica gel.